Brilliant Blue Dyes in Daily Food: How Could Purinergic System Be Affected?. (19th October 2016) - Ferreira, Leonardo Gomes Braga; Faria, Robson Xavier; Ferreira, Natiele Carla da Silva; Soares-Bezerra, Rômulo José
Abstract : Dyes were first obtained from the extraction of plant sources in the Neolithic period to produce dyed clothes. At the beginning of the 19th century, synthetic dyes were produced to color clothes on a large scale. Other applications for synthetic dyes include the pharmaceutical and food industries, which are important interference factors in our lives and health. Herein, we analyzed the possible implications of some dyes that are already described as antagonists of purinergic receptors, including special Brilliant Blue G and its derivative FD&C Blue No. 1. Purinergic receptor family is widely expressed in the body and is critical to relate to much cellular homeostasis maintenance as well as inflammation and cell death. In this review, we discuss previous studies and show purinergic signaling as an important issue to be aware of in food additives development and their correlations with the physiological functions.